PENGARUH PENGENDALIAN INTERN DAN PENERAPAN ANGGARAN BERBASIS KINERJA TERHADAP AKUNTABILITAS KINERJA (Studi Empiris di RSU Daerah Dr. R.M Djoelham Binjai) - Agnes Theresia Manik; Jatongam Nainggolan; Arison Nainggolan (Sekolah Tinggi Ilmu Ekonomi-LMII Medan, 2022)
The purpose of this study was to analyze the effect of internal control and the implementation of performance-based budgeting on accountability at the Dr. Regional General Hospital. RM Djoelham Binjai. The type of research used is causal research with a quantitative approach. The population in this study were 70 employees at the Regional General Hospital Dr. R.M. Djoelham Binjai with a sample of 60 employees. The research method used the census method, namely the entire population in this study was used as the research sample. The method of data analysis used multiple linear regression l model using SPSS software. This study uses quantitative data consisting of primary data obtained from questionnaires distributed to respondents. The results of this study indicate that simultaneously internal control and the implementation of performance-based budgeting have a significant effect on accountability at the Regional General Hospital Dr. R.M. Djoelham Binjai. Partially, internal control has a positive and significant effect on accountability, and the implementation of performance-based budgeting has a positive and significant impact on the accountability of the Regional General Hospital Dr. R.M. Djoelham Binjai. Meanwhile, internal control and implementation of performance-based budgeting on accountability at the Regional General Hospital Dr. RM Djoelham Binjai shows that the value of the determinant coefficient of R2 in the study is 0.508 or 50.8% which can be concluded that Accountability is influenced by Internal Control and Performance-Based Budgeting by 50.8% while 49.2% is influenced by other variables.